2015
DOI: 10.1645/14-608.1
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Life History and Ecological Aspects ofAllodero hylae(Annelida: Clitellata: Naididae), A Parasitic Oligochaete of Invasive Cuban Tree Frogs in Florida

Abstract: Given their ubiquitous nature, it is surprising that more oligochaete annelid worms (Annelida: Clitellata) have not adopted an endoparasitic lifestyle. Exceptions, however, are the understudied members of the genus Dero (Allodero) that parasitize the ureters of tree frogs and toads. This study experimentally explores the life cycle and host specificity of Allodero hylae, the worm's use of chemical cues in host searching, and its seasonal prevalence and abundance over a year-long collection period on the Florid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…However, it has recently been experimentally demonstrated that infections cause physical damage to the ureter that can kill young frogs (Andrews et al, 2015). Andrews et al (2015) also demonstrated that parasitic worms could be expelled from their host during urination. During intense infections, worms effectively spill over from the ureter into the urinary bladder and are susceptible to being voided with the urine.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it has recently been experimentally demonstrated that infections cause physical damage to the ureter that can kill young frogs (Andrews et al, 2015). Andrews et al (2015) also demonstrated that parasitic worms could be expelled from their host during urination. During intense infections, worms effectively spill over from the ureter into the urinary bladder and are susceptible to being voided with the urine.…”
Section: Introductionmentioning
confidence: 99%
“…This major morphological transformation provides the previously parasitic worms with the necessary anatomical structures of their free-living environment. The worms are capable of surviving in a free-living environment for an extended time period, although it is unclear under what circumstances free-living D. hylae seek anuran hosts (Andrews et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations